2019
DOI: 10.1177/2325967119836484
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Team Sport Volume Surveyed Between High School and Club Sport Coaches

Abstract: Background: Club sport participation is increasingly common among high school athletes. Sport participation characteristics may vary widely between the high school and club sport settings. However, there have been no large-scale comparisons of sport participation volume between high school and club teams from similar sports. Purpose/Hypothesis: The purpose of this study was to compare the sport participation characteristics of high school and high school–aged club teams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Tennis, swimming and diving, and fencing had the youngest mean ages of specialization (11.6, 12.4, and 12.8 years, respectively), while lacrosse, football, and field hockey had the oldest mean ages (17.2, 17.2, and 16.8 years). While not directly examining early sport specialization prior to the age of 12 years, a study of 343 NCAA Division-I athletes reported similar results, with 16.9% (58) of 343 athletes who reported specializing in their sport by their freshman year of high school 39 . The most common reasons cited for specializing were personal interest, potential scholarship opportunities, and skill level.…”
Section: Sport Scholarshipmentioning
confidence: 96%
See 1 more Smart Citation
“…Tennis, swimming and diving, and fencing had the youngest mean ages of specialization (11.6, 12.4, and 12.8 years, respectively), while lacrosse, football, and field hockey had the oldest mean ages (17.2, 17.2, and 16.8 years). While not directly examining early sport specialization prior to the age of 12 years, a study of 343 NCAA Division-I athletes reported similar results, with 16.9% (58) of 343 athletes who reported specializing in their sport by their freshman year of high school 39 . The most common reasons cited for specializing were personal interest, potential scholarship opportunities, and skill level.…”
Section: Sport Scholarshipmentioning
confidence: 96%
“…Therefore, individual coaches can adhere to the Pitch Smart pitch volume guidelines for all of the players on their team, while those players still accumulate excessive pitching volume overall because of their participation on multiple teams and in talent showcases 57 . Similarly, coaches from other sports have reported that while they monitor the sport volume of the athletes on their team, they do not have an effective method for tracking their athletes’ participation on other teams 58 . The rise of club sport teams, in which participants pay fees in order to participate on the team and in exclusive tournaments or showcases, has introduced a substantial financial conflict of interest that encourages year-round sport participation and increased sport participation volume 45 .…”
Section: Practical Solutions To Early Sport Specializationmentioning
confidence: 99%